Comparison between conventional open vesicolithotripsy and Percutaneous Vesicolithotomy (PCVL) in managing large bladder stone - Kamarulzaman, Mohd Nazli; Ab Rashid, Islah Munjih; Che Mohamed, Siti Kamariah; Ghazali, Hamid (2014)
Urinary bladder stone affected humankind since antiquity. It disease was noted in Egyptian manuscript more than 3500 BC. Along the history it management also evolve from perineum extraction to endoscopic management. Recent review article on urinary bladder stone management suggested percutaneous stone management for stone between 2-4cm sizes.